KADAR SERAT PANGAN DAN DAYA CERNA PATI NASI MERAH YANG DIPERKAYA KAPPA-KARAGENAN DAN EKSTRAK ANTOSIANIN DENGAN VARIASI METODE PENGOLAHAN - Nurhidajah -; Mary Astuti; Sardjono -; Agnes Murdiati; Yustinus Marsono (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Brown rice is one of the varieties of rice that are less popular because of the texture cooked more hard than white rice. Brown rice contain anthocyanins on the epidermis and is hypoglycemia. The nature of hypoglycemia brown rice also affected by the low digestibility of starch and dietary fiber contained in brown rice. Two things are influenced by the processing method when forming the rice into the rice. The purpose of this study was to evaluate the digestibility of starch and dietary fiber content of brown rice with a variety of processing. This research method is the enrichment of red rice with kappa-carrageenan 2% which aims to improve the organoleptic properties of texture and flavor, especially brown rice and anthocyanin extract 5ml / 100 grams of brown rice. The processing of brown rice into the rice is done with four processing method that is steamed, boiled, rice cooker and a control is raw rice. The results showed the highest levels of dietary fiber in brown rice processing method using a rice cooker, but statistically there was no effect of food processing methods with fiber. The highest starch digestibility on red rice by the method of the boiled and showed no effect of treatment with starch digestibility.Keywords: Brown rice, dietary fiber, starch digestibility and processing